2017
DOI: 10.3906/sag-1607-127
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the foramen magnum using cone beam computed tomography

Abstract: The aim of this study was to perform morphometric analysis of the foramen magnum (FM) using cone-beam computed tomography (CBCT). Materials and methods:This study included CBCT images of 190 individuals (88 males and 102 females). The sagittal and transverse diameters and circumference of the FM were measured. The shape of FM was classified as round, hexagonal, oval, egg-shaped, tetragonal, pentagonal, irregular A, and irregular B. The data were statistically analyzed with chi-square and t-tests to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
2
21
0
4
Order By: Relevance
“…Skull morphometric models specifically the basicranium and the area around foramen magnum were evaluated for their accuracies in sexing an unknown skeleton owing to its nature of being composed largely of indestructible hard tissue, the robusticity of the occipital bone and its protective anatomical position (Vidisha et al, 2019;Seifert et al, 2017). It provides a helpful tool for sex differentiation that could be used prior to performing destructive forms of testing studies like DNA analysis; or when such testing is not possible due to degradation as in cases of extensive heatdamage (Akay et al, 2017;Kanchan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Skull morphometric models specifically the basicranium and the area around foramen magnum were evaluated for their accuracies in sexing an unknown skeleton owing to its nature of being composed largely of indestructible hard tissue, the robusticity of the occipital bone and its protective anatomical position (Vidisha et al, 2019;Seifert et al, 2017). It provides a helpful tool for sex differentiation that could be used prior to performing destructive forms of testing studies like DNA analysis; or when such testing is not possible due to degradation as in cases of extensive heatdamage (Akay et al, 2017;Kanchan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] and Akay et al . [ 4 ] In case of all the above-mentioned studies, the mean transverse diameter and circumference of FM was found to be significantly higher in males than that of the females. In the current study also, the mean transverse diameter and circumference of FM of males was significantly higher than that of the females with P value 0.023 and 0.005, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Among various portions of the skull, the foramen magnum (FM) is one of the portion which helps forensic odontologists in sex discrimination. [ 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…The means of TD were 31.77±3.59 mm in males and 29.66±2.71 mm in females. Akay et al(by using CBCT) 2 reported the mean values of SD in males and females as 36.4 and 34.6 mm and TD as 31.2 mm and 29.8 mm, respectively. In the study of Tellioğlu et al 26 (by using CT), in males mean SD was 34.73 ± 2.21 mm, TD was 30.47 ± 2.25 mm, in females mean SD was 32.99 ± ± 2.65 mm, TD was 28.4 ± 2.72 mm.…”
Section: Discussionmentioning
confidence: 99%